Viacheslav Brodovyi's individual style features in the translation of George Martin's series "A song of ice and fire" (Linguostylistic Studies, 2021)
The article deals with the analysis of the individual style features of the translator Viacheslav Brodovyi. The goal of the study is to analyze the peculiarities of Viacheslav Brodovyi’s individual style of translation. The material for the research is an amateurtranslation of George Martin’s series “A Song of Ice and Fire” made by Viacheslav Brodovyi. The translator’s individual style has been investigated. His individual style comprises methods, ways, and strategies used to reproduce the idiosyncrasy of the translation. The translator seeks to get as close as possible to the hypothetical reader who perceives the text. The means of translation used by Vyacheslav Brodovyi have been analyzed. In most cases, the translator uses them to solve the problem of transmitting the national and cultural specific features of the language. The article describes the process of adaptation of the George Martin’s series “A Song of Ice and Fire”. Viachedlav Brodovyi uses the following ways of translation: transliteration, calque, word-formation technique, and descriptive translation to transfer or adapt the idea of the original work to the Ukrainian realities and adds a considerable number of dialectic words (rarely used and stylistically-marked vocabulary), bringing the series ofnovels “closer” to the ordinary Ukrainian reader. The translator has managed to convey accurately the essence laid down in the original work, without losing its individuality and identity. The analysis has shown that the main difficulties of translating were the expressive inversions, author's comparisons, onyms, as well as the differences in the lexical systems of two languages. Viacheslav Brodovyi’s has applied translation transformations, especially adaptations, which are characteristic features of the translator’s individual style. Thus, the individual style of the translator Viacheslav Brodovyi manifests itself in the stylistic dominance of deviations from the original, the usage of transliteration, calques, and descriptive translation.
Keywords: Key words: individual style of translator, calque, transliteration, word formation, descriptive translation.